PEWARISAN INTELEKTUAL DAN KHARISMA KEPEMIMPINAN DI PONDOK PESANTREN MUSTHAFAWIYAH PURBABARU MANDAILING - Abbas Pulungan (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2005)
Pesantren (Islamic Boarding School) Musthafawiyah Purbabaru is in the region Mandailing, North Sumatra, where the people are well-known as devoted islamic adherents and according to history, the leading figures of ulamas are mostly originated from this region. In their socioÂcultural life, the people of Mandailing has adopted a social system called Dalihan Na Tolu, which, in daily practice, has become less rigid compared with other regions in south Tapanuli, such as Angkola, Sipirok, and Padang Bolak. This Pesantren is the oldest in North Sumatera, and was established by Syekh Musthafa Husein in 1912. After his death in 1955, there have been three changes of leadership and currently it is under the leadership of his grandson, Haji Musthafa Bakri Nasution.